2009
DOI: 10.1007/s11434-009-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

Records of volcanic events since AD 1800 in the East Rongbuk ice core from Mt. Qomolangma

Abstract: Continuous Bi profile of the East Rongbuk (ER) ice core near Mt. Qomolangma reveals nine major volcanic events since AD 1800. Compared with Volcanic Explosivity Index (VEI), it shows that the concentrations of Bi in the ER ice core can reflect the major volcanic events within the key areas. This provides a good horizon layer for ice core dating, as well as a basis for reconstructing a long sequence of volcanic records from the Qinghai-Xizang (Tibet) Plateau ice cores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Owing to the relatively high‐accumulation rate (0.52 m w.e a −1 ), seasonal variations in water isotopes, soluble ions and trace elements are well preserved in the core, and were used to date ice in the core by counting annual layers [ Kaspari et al , 2008] to a depth of 86 m. The timescale was verified using high‐resolution measurements of bismuth (Bi) to identify major volcanic horizons, including Pinatubo, Agung and Tambora [ Kaspari et al , 2007]. Other eruptions may be more tentatively assigned [ Xu et al , 2009], however Krakatau, 1883 is not present in the Bi profile. Dating uncertainties are estimated to be about 5 years at 1534, at 86.8 m depth.…”
Section: Results and Interpretationmentioning
confidence: 99%
See 3 more Smart Citations
“…Owing to the relatively high‐accumulation rate (0.52 m w.e a −1 ), seasonal variations in water isotopes, soluble ions and trace elements are well preserved in the core, and were used to date ice in the core by counting annual layers [ Kaspari et al , 2008] to a depth of 86 m. The timescale was verified using high‐resolution measurements of bismuth (Bi) to identify major volcanic horizons, including Pinatubo, Agung and Tambora [ Kaspari et al , 2007]. Other eruptions may be more tentatively assigned [ Xu et al , 2009], however Krakatau, 1883 is not present in the Bi profile. Dating uncertainties are estimated to be about 5 years at 1534, at 86.8 m depth.…”
Section: Results and Interpretationmentioning
confidence: 99%
“…Figure 8 shows a comparison between the Bi profile [ Xu et al , 2009] and sulfate residual found from , and the averaged volcanic signature from polar ice cores [ Gao et al , 2008]. When comparing the ice core data with the volcanic index we use the published Kaspari et al [2007] timescale, which was tied to the 1815 Tambora signal.…”
Section: Results and Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…As the lowest EF c values are above 30 for these elements in the samples, it is likely that volcanic contributions for these elements are significant. The volcanic events occurred during 2005 ejected materials into the troposphere that can be transported via atmospheric circulation and deposited on the surface of the snow in the high altitude Himalayan region (Xu et al 2009a). For example, the eruption of Barren Island volcano (12°16 0 40 00 N, 93°51 0 30 00 E), India, began on 26 May 2005 and stopped on 23 December 2007 and the eruption column of ash particles attained a height of more than 300 m (Pal et al 2007).…”
Section: Contribution From Natural Sourcesmentioning
confidence: 99%